[PP.32.01] MORTALITY FROM BLOOD-PRESSURE-RELATED DISEASES IN BRAZIL FROM 1980–2010. (September 2016) - Moreira, H.; Reis, A.; Rodrigues, R.; Sousa, A.; Barros, C.; Araujo, Y.; Jardim, T.; Sousa, A.; Souza, W.; Jardim, P.
Abstract : Objective: To estimate the mortality attributable to Hypertension in Brazil from 1980 to 2010 Design and method: Data about deaths from cardiovascular diseases in Brazil from 1980 to 2010 were obtained from the Ministry of Health/DATASUS. Besides the specific mortality from hypertensive diseases (ICD10 I10-I13 and corresponding ICD9 codes), cardiovascular mortality attributable to HTN was calculated using 2000 s Global Burden of Disease study estimation (Lancet 2008;371:1513–18). According to this study, mortality attributable to high blood pressure (> or = 115 mmHg systolic) was estimated by 54% of all deaths from CeVD (ICD10 I60–69 and corresponding ICD9), 47% of deaths from coronary artery disease (CAD) (ICD10 I20-I25 and corresponding ICD9), and 25% of deaths from other cardiovascular diseases (ICD10 I26–28, I34–37, I44–51, I70–99, and corresponding ICD9) can be attributed to HTN. Mortality rates (deaths/100, 000 people) were adjusted by gender and age group using the direct method. For trend analysis data were adjusted by Poisson regression model. Results: Approximately 3, 660, 313 deaths could be attributed to HTN over the analyzed period. Those deaths accounted for 11.4% of all deaths recorded in 1980, increasing proportionally to 14.5% of all deaths in 2010. Cerebrovascular diseases were the main cause of those deaths (37.4%), followed by CAD (29.0%). There was an increase of mortality rates attributed to HTN in this period: adjusted mortality raised from 74.7 to 89.8/100, 000 people (P-value < 0.01), which was more pronounced among women (66.8 to 81.8/100, 000, R 2 = 0.627). Conclusions: Between 1980 and 2010, there was an increase in mortality rates for causes directly attributable to high blood pressure in Brazil. Despite the limitations of risk estimate studies, there are evidences that the hypertension control is still not ideal in Brazil, with significant impact on related mortality.